Decreased natural killer cell activity as a potential predictor of hypertensive incidence - Lee, Yun-Kyong; Suh, Eunkyung; Oh, Hyoju; Haam, Ji-Hee; Kim, Young-Sang (Frontiers in Immunology, 2024)
Introduction Blood pressure is closely linked with immune function. This study examined the association between natural killer (NK) cell activity (NKA) and blood pressure and the development of hypertension according to NKA levels. Methods This study enrolled 1543 adults who underwent NKA measurement and serial health check-ups at a medical center in Korea. NKA was estimated as the concentration of IFN-γ in the incubated whole blood containing a patented stimulatory cytokine. The participants were categorized into quartiles according to their NKA levels. Participants without hypertension were followed up, and the development of hypertension was compared according to the quartiles. Results The prevalence of hypertension was not different among the NKA quartiles, whereas blood pressures significantly decreased, followed by an increment of quartiles (systolic blood pressure of 119.0 in Q1 and 117.0 in Q4, P-trend = 0.018). Over a mean follow-up period of 2.13 years, hypertension developed in 156 of 1170 individuals without baseline hypertension. The hazard ratio of Q4 compared with Q1 was 0.625 (95% CI: 0.397–0.983; p = 0.042). Conclusion In conclusion, our findings indicate a correlation between lower NKA and higher blood pressure and the development of incident hypertension. This may suggest a potential protective role of NK cells against endothelial dysfunction. Further research is necessary to elucidate the specific relationship between immune functions and endothelial function.